Antimicrobial Resistance Profiles of Adherent Invasive Escherichia coli Show Increased Resistance to β-Lactams - Margarita Martinez-Medina; Francesco Strozzi; Belén Ruiz Del Castillo; Natalia Serrano-Morillas; Nuria Ferrer Bustins; Luis Martínez-Martínez (MDPI AG, 2020)
The adherent invasive Escherichia coli (AIEC) pathotype has been associated with the aetiology of Crohn's disease (CD). Scarce reports have shown the antimicrobial resistance (AMR) profiles of AIEC. Despite antibiotics not being recommended to treat CD, antimicrobial therapy could be useful in stratified patients, such as AIEC carriers. We examined the antimicrobial resistance profiles of AIEC strains to identify which therapies could be effective or confer a risk for such patients. Phenotypic resistance to 30 antimicrobials was tested according to CLSI standards. AIEC (n = 22) and non-pathogenic E. coli (non-AIEC) strains (n = 37) isolated from the gut mucosa of 31 CD patients and 18 controls were studied. De novo genome sequencing was carried out for 39 of the 59 strains, and AMR genes were searched using the DeepARG database in these genomes and 33 additional AIEC publicly available genomes. The strains isolated from CD and controls showed similar phenotypic AMR profiles. The genomic analysis did not reveal an increased prevalence of AMR genes. However, AIEC strains were more frequently resistant to β-lactams than non-AIEC strains (11 AIEC (50%) and 5 non-AIEC (22%) strains were resistant to at least one β-lactam; p < 0.042). Two AIEC strains were resistant to expanded-spectrum cephalosporins. One strain carried a plasmid-mediated AmpC β-lactamase (CMY-69), and the other presented mutations in the promotor of the intrinsic chromosomal AmpC related to the hyperproduction of this enzyme. The rest of the strains were resistant to β-lactams not including expanded-spectrum cephalosporins. The majority carried TEM-related β-lactamases. Genomic analysis including external AIEC revealed that the gene sul1 encoding for sulphonamide resistance was more frequent in AIEC strains than non-AIEC strains (34.6% vs. 9.5%, p = 0.030). AMR in AIEC is a matter of concern regarding the putative implication of the pathotype in CD. The high proportion of AIEC resistant to β-lactams warrants caution about the risk there may be in the use of these antimicrobials in AIEC-colonized CD patients.